After Peter Doig's "Music of the Future" - Joseph Mulholland (Caribbean Studies Students' Union, 2022)
The poem is loosely inspired by Peter Doig's painting "Music of the Future" and reimagines the night scene that is depicted in the painting. The poetic voice is rooted in a deep sense of place while simultaneously speaking from the outer edges of that place, creating a liminal space through poetic images and narrative.